Stability analysis of an open cut slope in Wardha valley coal field - Verma D.; Kainthola A.; Thareja R.; Singh T.N. (My University, 2025)
Open cast mines are the prime source of coal production in India. Due to an increase in coal demand, deeper surface mines are being planned to ensure better productivity with enhanced safety of these mines. The safe working environment and continuous production of the coal calls for the safe and stable design of cut slopes. The stability analysis of this slope requires in depth geotechnical investigation which are aided by result orientated stability assessment using empirical methods and numerical simulation. In the present study, a slope was examined to understand the mechanism and comparisons were made with field observations. The investigation has involved a 32m high cut slope from an open cast mine in Wardha valley coal field which has been analyzed using a two dimensional numerical simulation. The bench slope consisted of a low strength sandstones, shales and clay sequence. Hoek-Brown strength parameters established and used as input parameters in the model. The results indicate that the slope is critically stable and may lead to failure without warning and needs proper attention. © 2013 Geological Society of India.